The elephants of Burkina Faso, West Africa - Clive Spinage (Pachyderm)
The paper discusses the distribution of elephants in Burkina Faso. As the range is outside the tropical forest zone the savanna elephant is present. In general the body size is large but the tusks are relatively small. The major populations are to be found in 'W' and Po National Parks; Deux-Bale, Singou and Rama Reserves, Arli (Arly) and West Pama regions; and Nazinga area. The extent of poaching is difficult to assess, but there does not appear to be any large-scale or well organized programme. Population estimates, established with the aid of both ground and air surveys, for 1981/82 are approximately 2920 animals found in eight areas.